2018
DOI: 10.1200/cci.18.00024
|View full text |Cite
|
Sign up to set email alerts
|

Development of Health Pathways to Standardize Cancer Care Pathways Informed by Patient-Reported Outcomes and Clinical Practice Guidelines

Abstract: Purpose High-quality symptom management and supportive care are essential components of comprehensive cancer care. We aimed to describe the development of an evidence-based automated decisional algorithm for patients with cancer that had specific, actionable, clinical, evidence-based recommendations to improve patient care, communication, and management. Methods We reviewed existing literature and clinical practice guidelines to identify priority domains of patient care and potential clinical recommendations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…8 Prince of Wales Clinical School, University of New South Wales, Sydney, NSW 2052, Australia. 9 Faculty of Health and Medical Sciences, University of Adelaide, Adelaide, SA 5000, Australia. 10 College of Medicine and Public Health, Flinders University, Adelaide, SA 5042, Australia.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Prince of Wales Clinical School, University of New South Wales, Sydney, NSW 2052, Australia. 9 Faculty of Health and Medical Sciences, University of Adelaide, Adelaide, SA 5000, Australia. 10 College of Medicine and Public Health, Flinders University, Adelaide, SA 5042, Australia.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…A systematic review found that PROMs may be useful in cancer care, to longitudinally monitor and respond to the impacts of treatments or symptoms on patients' lives [8]. For example, some PROMs are designed to automatically trigger the provision of tailored information to patients to help them address their symptoms and side-effects [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although a range of tools are available (e.g., the DT), such tools are not routinely implemented in survivorship settings. Screening for survivors' needs and the prioritization of care often requires a highly contextualized approach consistent with the local setting and resources [5]. Implementation of a standardized method to screen for, and manage, the immediate needs of cancer patients at each cancer center is likely helpful for future management of crisis and pandemic situations.…”
mentioning
confidence: 99%
“…While there is a wide range of PROs that could be assessed during cancer treatment and in survivorship, several efforts have aimed to identify key domains relevant to improving outcomes in cancer care. For example, a clinical advisory group identified priority domains and measures to enhance cancer care, which included distress and symptoms [12][13][14] and unmet needs [15]. Girgis et al, then developed clinical recommendations from these domains, mapped them into well-being categories, and demonstrated that these recommendations could algorithmically provide automated clinical feedback [15].…”
Section: Digital Healthmentioning
confidence: 99%
“…For example, a clinical advisory group identified priority domains and measures to enhance cancer care, which included distress and symptoms [12][13][14] and unmet needs [15]. Girgis et al, then developed clinical recommendations from these domains, mapped them into well-being categories, and demonstrated that these recommendations could algorithmically provide automated clinical feedback [15]. There is also concern that the use of structured questionnaires to assess PROs may limit the ability to capture the broad range of symptoms experienced by patients during treatment.…”
Section: Digital Healthmentioning
confidence: 99%